Flood Inundation Generation Mechanisms and Their Changes in 1953–2004 in Global Major River Basins. Issue 22 (16th November 2019) - Mao, Yuna; Zhou, Tian; Leung, L. Ruby; Tesfa, Teklu K.; Li, Hong‐Yi; Wang, Kaicun; Tan, Zeli; Getirana, Augusto
Abstract: Despite the serious threats posed by floods, the driving mechanisms of floods are still not well understood. Here we apply a physically based inundation model coupled with a river routing model (Model for Scale Adaptive River Transport (MOSART)) within the Energy Exascale Earth System Model (E3SM) framework to investigate flood inundation dynamics. After calibration using observed streamflow and satellite‐derived flood extent, the model is used to simulate global flood inundation from 1953 to 2004. The mean date and seasonality of annual maximum flood, defined based on flood extent, exhibit significant regional differences across 16 major basins. Generally, soil moisture and monthly maximum daily rainfall (MMR) are the dominant drivers of flood in tropical basins while monthly maximum daily snowmelt (MMS) is the dominant driver in high‐latitude basins. From 1953–1982 to 1975–2004, significant changes in flood generation mechanisms are found in some basins such as Amazon, Lena, Yenisey, and Kolyma. Analysis of the rainfall seasonality and water balance at grid scale reveals a stronger rainfall seasonality in the Amazon during the later period that increases the synchrony between extreme rainfall and wet soil. With high antecedent soil moisture coinciding with rainfall, MMR contributes more to flood in the later period. Fewer extreme rainfall events and increasing soil moisture reduced the contribution of MMR and increased the role of MMS in floods in the Lena and Yenisey basins, respectively. Lastly, increased soil moisture and frequency of large MMS reduced the contribution of the latter to floods in the Kolyma basin. Key Points: Global flood inundation dynamics are simulated with a physically based inundation model coupled with a river routing model Flood date, seasonality, and generation mechanisms show large spatial variability across 16 major river basins around the world Rainfall importance to flood decreased in most rainfall‐driven basins and snowmelt importance decreased at high latitudes in 1953–2004